Stream Hydrological Fragmentation Drives Bacterioplankton Community Composition - Fazi, Stefano (Public Library of Science, 2013)
In Mediterranean intermittent streams, the hydrological fragmentation in summer and the successive water flow re-convergence in autumn allow exploring how local processes shape the microbial community within the same habitat. The objectives of this study were to determine how bacterial community composition responded to hydrological fragmentation in summer, and to evaluate whether the seasonal shifts in community composition predominate over the effects of episodic habitat fragmentation. The bacterial community was assessed along the intermittent stream Fuirosos (Spain), at different levels of phylogenetic resolution by in situ hybridization, fingerprinting, and 16S rRNA gene sequencing. The hydrological fragmentation of the stream network strongly altered the biogeochemical conditions with the depletion of oxidized solutes and caused changes in dissolved organic carbon characteristics. In the isolated ponds, beta-Proteobacteria and Actinobacteria increased their abundance with a gradual reduction of the alpha-diversity as pond isolation time increased. Moreover, fingerprinting analysis clearly showed a shift in community composition between summer and autumn. In the context of a seasonal shift, the temporary stream fragmentation simultaneously reduced the microbial dispersion and affected local environmental conditions (shift in redox regime and quality of the dissolved organic matter) tightly shaping the bacterioplankton community composition.